News as geopolitics: China, CGTN and the 2020 US presidential election. Issue 1 (2nd January 2023) - Colley, Thomas; Moore, Martin
ABSTRACT: Recently, authoritarian states have invested heavily in state-sponsored international news. Some states have instrumentalised this news geopolitically, with Russian electoral interference especially prominent. In comparison, we know less about how China's international news outlets cover – and try to influence – other countries' politics. This article asks whether China used its state-sponsored media to influence the 2020 US election. It examines CGTN's coverage of the election and the 2021 Capitol riots, across its website, Twitter, Facebook and YouTube. Tellingly, it finds no concerted effort to influence the outcome. CGTN's coverage was mostly cautious and neutral. Contrastingly, its geopolitical coverage of the US and China was entirely one-sided, persistently excoriating the US while praising China. We identify three news values differentiating CGTN's coverage: deference, relevance (to China), and national sovereignty. These news values reveal CGTN's geopolitical function: to convey Chinese media's apparent impartiality, while promoting China at its competitors' expense.